Effects of self-assembly process of latex spheres on the final topology of macroporous silica - Barros, D. A.; Hisano, C.; Bertholdo, R.; Schiavetto, M. G.; Santilli, C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2005)
This paper surveys the topology of macroporous silica prepared using latex templates covering the submicrometric range (0.1-0.7 mu m). The behavior of latex spheres in aqueous dispersion has been analyzed by dynamic light scattering (DLS) measurement indicating the most appropriate conditions to form well-defined cubic arrays. The optical behavior of latex spheres has been analyzed by transmittance and reflectance measurements in order to determine their diameter and filling factor when they were assembled in bidimensional arrays. Macroscopic templates have been obtained by a centrifugation process and their crystalline ordering has been confirmed by porosimetry and scanning electron microscopy. These self-assembled structures have been used to produce macroporous silica, whose final topology depends on the pore size distribution of the original template. It has been seen that latex spheres are ordered in a predominant fcc arrangement with slipping of tetragonal pores due to the action of attractive electrostatic interactions. The main effect is to change the spherical shape of voids in macroporous silica into a hexagonal configuration with possible applications to fabricate photonic devices with novel optical properties. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: latex spheres; photonic crystals; chemical template; macroporous silica; porous material; self-assembly; thin films; colloid stability